Development of tri-layer antioxidant packaging systems based on recycled PLA/sodium caseinate/recycled PLA reinforced with lignocellulosic nanoparticles extracted from yerba mate waste - Marina Patricia Arrieta; Freddys Beltran; Sara Soledad Abarca de las Muelas; Gerald Gaspar; Rafael Sanchez Hernandez; Maria Ulagares de la Orden; Joaquin Martinez Urreaga (eXPRESS Polymer Letters)
Tri-layer films based on glycerol-plasticized sodium caseinate film (SC) as the middle layer and two outer layers of mechanically recycled poly(lactic acid) (RPLA) were successfully developed. Additionally, the internal RPLA-based layer was loaded either with 1 or 3 wt% of lignocellulose nanoparticles extracted from yerba mate waste (YMNs) to obtain antioxidant-active packaging formulations. YMNs were also surface modified with a surfactant to increase the interfacial adhesion and improve their dispersion into the polymeric matrix. The tri-layer system composed of YMNs loaded nanocomposites (RPLA/SC/RPLA-YMN1 and RPLA/SC/RPLA-YMN3) exhibited an improved oxygen barrier compared to the nonreinforced system counterpart (RPLA/SC/RPLA). The high water vapor permeability of SC was reduced in tri-layer systems, ascribed to the protection of the middle SC layer by the hydrophobic RPLA layers at both sides. The improved performance of all these properties was ascribed to the good adhesion between PLA and SC layers, ascribed to hydrogen bonding interactions. Furthermore, the obtained tri-layer structures showed effective antioxidant ability for fatty food, as it was demonstrated by release studies conducted in a fatty food simulant and further analysis of the radical-scavenging activity showing good antioxidant properties (RPLA/SC/RPLA-YMN1 = 36.8±2.5 GA mg/dm2 film and RPLA/SC/RPLA-YMN3 = 81.1±2.5 Gallic Acid mg/dm2 film). Finally, the tri-layer films were disintegrated under composting conditions in 17 days. Thus, the results show the potential of the mechanical recycling process of PLA as a sustainable alternative to revalorizing PLA waste, while the revalorization of yerba mate waste shows its interest by easily providing the materials with antioxidant properties. Finally, the tri-layer bio-based and biodegradable active formulations resulted in interesting materials for fatty foodstuffs.